RESPONSE OF STRAWBERRY GROWTH, YIELD AND MARKETABLE FRUIT QUALITY TO SPRAYING WITH MORINGA LEAF EXTRACT, CALCIUM AND POTASSIUM SILICATE - Mohammed, Rasha R; Majeed, B H (Iraqi journal of agricultural science, 2024)
Tow field and storage experiments were carried out to evaluate the effect of foliar application of moringa leaf extract, calcium, and potassium silicate on the growth, yield, and quality characteristics of strawberry fruits. The field experiment included 27 treatments: Foliar application of moringa leaf extract at the concentrations of 0, 5, and 10% which were symbolized as M0, M1, and M2 respectively, calcium at the concentrations of 0, 1, and 2 g. L-1, which were symbolized as Ca0, Ca1, and Ca2 respectively, and potassium silicate at the concentrations of 0, 1.25, and 2.50 ml. L-1 which were symbolized as S0, S1, and S2 respectively, with three replicates. The storage experiment was carried out according to the same design that was applied in the first experiment, at a temperature of 0-2 ºC. The results revealed that the M2 treatment significantly increased Plant height, leaf number, crown diameter, flowering cluster number, plant yield, Fruit T.S.S, Vitamin C, as well as maintaining the T.S.S and Vitamin C after storage, and reduced the fruits distortion. The treatment of Ca1 recorded a significant increment in the growth and yield parameters and reduced fruit distortion, Also the treatment of S2 recorded significant values of the above-mentioned parameters, Moreover, the interactions of M2Ca1, M2S2, and Ca1S2 and the triple interaction of M2Ca1S2 recorded the highest values of the studied parameters.